Length effects of cylindrical polymer brushes on their in vitro and in vivo properties. (2nd October 2019) - Zhang, Zhengkui; Zhang, Ling'e; Zhao, Jiaojiao; Li, Cheng; Wu, Wei; Jiang, Xiqun
Abstract : Cylindrical polymer brushes with different lengths were synthesized and length effects on their biological properties were obtained. Abstract : Understanding the relationship between the morphology and biological performance of nanomaterials is very important for their biomedical applications. However, most of the published research focused on spherical systems. The biological properties of the anisotropic nanomaterials have not been studied enough. In this study, we synthesized three sets of cylindrical polymer brushes (CPBs) with different lengths (∼34, 60 and 119 nm) by taking advantage of controlled radical polymerization and Cu(i )-catalyzed alkyne–azide click chemistry. These CPBs had one-dimensional wormlike morphology, the same chemical structure and diameter, desirable water solubility, abundant amino groups and narrowly distributed lengths. These characteristics encouraged us to study length effects on their in vitro and in vivo properties. We demonstrated that longer CPBs had higher cellular uptake, lower tissue permeability, shorter blood circulation time, lower tumor accumulation and rapider body clearance than their shorter counterparts. This work might provide important guidance for the design of biomedical nanomaterials.